A Teacher’s Lesson Narrative Regarding Statistics Investigation - Grando, Regina Célia (2014)
In this paper we analyze the lesson narrative of a mathematics teacherfor the Elementary School. She is a member of a group developing a collaborativeresearch as part of the ‘Educational Observation Project’, aiming toinvestigate mathematical literacy and the teaching education practices ofmathematics teachers. In her narrative, she describes the statistic investigationprocess developed with a 1st grade group. There is evidence revealingthe teacher’s hints of learning related to the children’s statistics literacy,mainly referring to the development of graphical language, as well as evidenceof ownership of literacy practices by the teacher.